COVID-19 Pandemic Leading to the Accelerated Development of a Virtual Health Model for Isotretinoin. Issue 1 (January 2021) - Kane, Sierra; Admani, Shehla
Abstract : ABSTRACT: Isotretinoin is a highly efficacious medication for the treatment of acne vulgaris; however, its prescription is subject to the strict requirements of the iPLEDGE restricted distribution program. These requirements have placed significant financial, time, and logistical burdens on patients taking the medication. The stay-at-home ordinances enacted by many states during the 2019 novel coronavirus (COVID-19) global pandemic have accelerated previous trends toward utilization of telehealth and decreased laboratory monitoring in the care of patients on isotretinoin. Recent changes to the iPLEDGE program allowing use of at-home pregnancy tests to meet monthly pregnancy test requirements during the pandemic have increased availability of testing options for patients of child-bearing potential on isotretinoin. The change to use of at-home pregnancy test monitoring as well as long-term trends toward increasing access to isotretinoin through the use of telehealth are discussed.